SYUJET POETIKASIDA MIFOLOGIK TALQIN USTUVORLIGI - Allanazarova, F.K. (SCIENCE and SOCIETY, 2025)
In this paper, each writer's interpretation shows traits related to human destiny in a different way. Mythopoetic interpretation takes some control over stories with a seemingly simple plot. The combination of symbols and mythology will play a key role in the emergence of a new image of man.
Keywords: story; legend; oppression; violence; symbol; harmony; truth; character; means; body; plot; presence